Virtual CP@clinic / Virtuel PC@clinique - Agarwal, Gina; AlShenaiber, Leena (My University, 2021)
[English] CP@clinic has responded and adapted to the COVID-19 pandemic. The program has specific components to facilitate virtual program implementation, which are supported by a SMART database. [Français] PC@clinique répond et s'adapte à la pandémie de COVID-19. Le programme comprend des composants spécifiques pour faciliter la mise en oeuvre du programme virtuel, qui sont soutenus par une base de données INTELLIGENTE.
Keywords: Community Paramedicine; Primary Care; Vulnerable Populations; Paramedic Service; Paramedics; Virtual Care